Extraction approaches for the isolation of some POPs from lipid-based environmental and food matrices: A review - Carriera Fabiana; Di Fiore Cristina; Iannone Alessia; Maio Monica; Avino Pasquale (Reviews in Analytical Chemistry)
This review examined various analytical approaches for extracting some persistent organic pollutants (POPs) from environmental and food matrices containing lipid components. The impact of the lipid component on the extraction of such hazardous chemicals from fatty matrices is well-known due to their lipophilicity. The analysis of the scientific literature revealed different approaches, typically characterized by the use of a solvent mixture that leads to the co-extraction of lipid components, followed by one or more laborious clean-up steps to remove the interferents from the matrix. Despite the differences in the approaches used, the observed recoveries are high, >80%. Additionally, it was found that the same technique could extract different contaminants from various matrices, resulting in a loss of selectivity of the method used. The uncertainties suggested in this review consider (i) the actual extraction of POPs with polar solvents (e.g., acetonitrile) from lipid component, for which POPs may have higher retention; (ii) the use of laborious, long cleaning steps (e.g., polar and non-polar adsorbent phases) could affect recoveries; (iii) the absence of studies investigating the concrete and constant distribution of POPs between extractive solvent/lipid component and solvent/adsorbent phase. Further, the recent application of eutectic solvents was discussed as a promising approach towards a green chemistry procedure.